Hepatic CEACAM1 Over-Expression Protects Against Diet-Induced Fibrosis and Inflammation in White Adipose Tissue - Lester, Sumona G.; Russo, Lucia; Ghanem, Simona S.; Khuder, Saja S.; DeAngelis, Anthony M.; Esakov, Emily L.; Bowman, Thomas A.; Heinrich, Garrett; Al-Share, Qusai Y.; McInerney, Marcia F.; Philbrick, William M.; Najjar, Sonia M. (Frontiers in Endocrinology, 2015)
CEACAM1 promotes insulin extraction, an event that occurs mainly in liver. Phenocopying global Ceacam1 null mice (Cc1–/–), C57/BL6J mice fed a high-fat (HF) diet exhibited reduced hepatic CEACAM1 levels and impaired insulin clearance, followed by hyperinsulinemia, insulin resistance, and visceral obesity. Conversely, forced liver-specific expression of CEACAM1 protected insulin sensitivity and energy expenditure, and limited gain in total fat mass by HF diet in L-CC1 mice. Because CEACAM1 protein is barely detectable in white adipose tissue (WAT), we herein investigated whether hepatic CEACAM1-dependent insulin clearance pathways regulate adipose tissue biology in response to dietary fat. While HF diet caused a similar body weight gain in L-CC1, this effect was delayed and less intense relative to wild-type (WT) mice. Histological examination revealed less expansion of adipocytes in L-CC1 than WT by HF intake. Immunofluorescence analysis demonstrated a more limited recruitment of crown-like structures, and qRT-PCR analysis showed no significant rise in TNFα mRNA levels in response to HF intake in L-CC1 than WT mice. Unlike WT, HF diet did not activate TGF-β in WAT of L-CC1 mice, as assessed by Western analysis of Smad2/3 phosphorylation. Consistently, HF diet caused relatively less collagen deposition in L-CC1 than WT mice, as shown by Trichrome staining. Coupled with reduced lipid redistribution from liver to visceral fat, lower inflammation and fibrosis could contribute to protected energy expenditure against HF diet in L-CC1 mice. The data underscore the important role of hepatic insulin clearance in the regulation of adipose tissue inflammation and fibrosis.